2008
DOI: 10.1542/peds.2007-1115g
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinating Adolescents in High-Risk Settings: Lessons Learned From Experiences With Hepatitis B Vaccine

Abstract: Meeting the health needs of adolescents who live in high-risk settings such as homeless shelters, migrant camps, juvenile detention centers, prisons, and other types of residential facilities presents many challenges. Although there is no doubt that adolescents in many high-risk settings are at increased risk for hepatitis B and human papillomavirus, acute medical and psychological problems may consume all of the provider's time and resources. Potential health threats such as vaccinepreventable diseases must n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Our data could not be used to determine if these laws had an impact on vaccination rates, because state-level data were not available. Nontraditional settings, such as sexually transmitted disease (STD) clinics, juvenile detention centers, and homeless shelters, have been shown to successfully adopt vaccination programs for adolescents [28]. Consent for vaccination still needs to be addressed at each venue depending on the status of the adolescent and the legal environment in the state [29].…”
Section: Discussionmentioning
confidence: 99%
“…Our data could not be used to determine if these laws had an impact on vaccination rates, because state-level data were not available. Nontraditional settings, such as sexually transmitted disease (STD) clinics, juvenile detention centers, and homeless shelters, have been shown to successfully adopt vaccination programs for adolescents [28]. Consent for vaccination still needs to be addressed at each venue depending on the status of the adolescent and the legal environment in the state [29].…”
Section: Discussionmentioning
confidence: 99%
“…These rates have been substantially lower than for young children and below Healthy People 2010 goals [3,4]. Healthcare professionals and public health officials are focused on better understanding barriers to adolescent vaccination and how to overcome them [5][6][7][8][9][10][11][12][13]. Strategies proposed for increasing vaccine delivery include increasing delivery in medical homes and other sites, and use of school entry requirements.…”
mentioning
confidence: 99%
“…The high cost of the vaccines and the difficulty in reaching adolescents for vaccination and other health care issues (see Szilagyi et al, 87 Broder et al, 88 and Sneller et al 89 ) have suggested that a new paradigm may be necessary. We must be able to explain to adolescents, their parents, and public health decisionmakers the special place that vaccines hold among clinical preventive services (see Broder et al 88 ).…”
Section: Discussionmentioning
confidence: 99%
“…90 However, immunization advocates need to concede that numerous other clinical 90 and community preventive services are of tremendous value in reducing the burden of disease and injury among adolescents. 89 Furthermore, the challenge of implementing even the most strongly recommended preventive services cannot be underestimated. 90,91 Analyses of the cost-effectiveness of mature vaccination programs and comparisons between vaccines and other preventive services continue to be conducted and are essential to guiding public policy.…”
Section: Discussionmentioning
confidence: 99%